Attributes of children and adolescents with avoidant/restrictive food intake disorder - Helene Keery; Sarah LeMay-Russell; Timothy L. Barnes; Sarah Eckhardt; Carol B. Peterson; Julie Lesser; Sasha Gorrell; Daniel Le Grange (Journal of Eating Disorders, 2019)
Abstract Background Avoidant/Restrictive Food Intake Disorder (ARFID) is a comparatively new DSM-5 diagnosis. In an effort to better understand this heterogeneous patient group, this study aimed to describe the physical and psychological attributes of children and adolescents with ARFID, and to compare them to patients with full-threshold or atypical anorexia nervosa (AN). Methods Children and adolescents aged 7-to-19 years (N = 193) were examined upon presenting at a pediatric eating disorder center between July 2015 and December 2017. Data included diagnosis assessed via the semi-structured Eating Disorder Examination interview along with measures of anthropometrics, depression, anxiety, self-esteem, perfectionism and clinical impairment. Results Compared to AN and atypical AN (n = 87), patients with ARFID (n = 106) were significantly younger (12.4 vs. 15.1 years, p < .0001), male (41% vs. 15%, p < .0002), and were more likely to be diagnosed with at least one co-morbid DSM-5 diagnosis (75% vs. 61%, p = .04). Patients with ARFID were less likely to be bradycardic (4.7% vs. 24.1%, p < .0001), amenorrheic (11.1 and 34.7%, p = .001), admitted to the hospital (14.2% vs. 27.6%, p = .02), and have a diagnosis of depression (18.9% vs. 48.3%, p < .0001). Patients with ARFID were significantly less likely to experience acute weight loss vs. chronic weight loss as compared with those with AN or atypical AN (p = .0001). On self-report measures, patients with ARFID reported significantly fewer symptoms of depression, anxiety, perfectionism, clinical impairment, concerns about weight and shape, and higher self-esteem than patients with AN or atypical AN (all ps < .0001). No differences were observed by race, anxiety disorder, orthostatic instability, suicidal ideation, and history of eating disorder treatment. Conclusions Study results highlight the clinical significance of ARFID as a distinct DSM-5 diagnosis and the physical and psychological differences between ARFID and AN/atypical AN. The novel finding that ARFID patients are more likely than those diagnosed with AN to experience chronic, rather than acute, weight loss suggests important related treatment considerations.